NATION-STATE AND ITS SPECIALIZED GARDENING STRATEGIES: HEALTH AS A FOCUS OF ACTION - Gomes, Ivan Marcelo; Fernandez Vaz, Alexandre; Assmann, Selvino José (Educere et Educare, 2000)
This article aims at demonstrating how some strategies for a healthy life, linked to state gardening, have been incorporated in the national scenario. We do not seek a detailed historical review, but only to outline a scenario in order to establish points of convergence with the search for order as a typical expression of the Modernity. In this perspective, this article focuses, although not exhaustively, some aspects linked to Physical Education, taking as object of study the advice for being a healthy person. However, it is important to highlight that, although the area of Physical Education covers this debate, this is not a study limited to or centered in this area; moreover, it does not seek the origins or the accuracy of the specificities of this field. In order to join the debate on the search for order, we have identified that such modern premise has allowed the appearance of different strategies with a similar purpose. The state strategies – or even the institutional strategies linked, to a greater or lesser degree, to the State – subsidized by the experts have enabled a confluence of factors, involving several agents in the search for order. Keywords: State; Modernity; Public politics of health.